Highly defective 1T-MoS2 nanosheets on 3D reduced graphene oxide networks for supercapacitors. (November 2019) - Naz, Raheela; Imtiaz, Muhammad; Liu, Qinglei; Yao, Lulu; Abbas, Waseem; Li, Tengfei; Zada, Imran; Yuan, Yang; Chen, Wenshu; Gu, Jiajun
Abstract: Highly defective molybdenum disulfide (MoS2 ) nanosheets of 1T phase are synthesized on a three-dimensional reduced graphene oxide (3D RGO) network through a one-pot hydrothermal method. By switching the reaction time, the resulting MoS2 's phases (1T or 2H) and defect-density are successfully controlled. Reducing the reaction time from 20 to 6 h increases the defect-density and induces a phase transition from hybrid 2H/1T to 1T phase. High defect-density coupled with high 1T-phase portion in MoS2 nanosheets/RGO heterostructures enhances the electrochemical performance for supercapacitor application by inducing additional active sites, which provide fast charge transfer rate and a large number of ion diffusion channels. Among all samples, the defect rich 1T-phase MoS2 nanosheets/RGO heterostructure synthesized in 6 h (M/RGO-6) gives an outstanding specific capacitance of 442.0 F g −1 at a current density of 1 A g −1 . The M/RGO-6 also exhibits excellent cycling stability with capacitance retention of 90.3% over 1000 cycles at 5 A g −1 . These make M/RGO-6 attractive to the electrode of high-performance supercapacitors. Graphical abstract: Image 1